Isolation and identification of a novel peptide from zein with antioxidant and antihypertensive activities. Issue 12 (30th September 2015) - Wang, Yanwei; Chen, Haixia; Wang, Xiuming; Li, Shuqin; Chen, Zhongqin; Wang, Jingya; Liu, Wei
Abstract : The aim of this study is to isolate and identify a novel corn peptide (CP) from zein with antioxidant and antihypertensive activities based on bioactive-guided isolation procedures. Abstract : The aim of this study is to isolate and identify a novel corn peptide (CP) from zein with antioxidant and antihypertensive activities based on bioactive-guided isolation procedures. Zein was hydrolyzed by using double enzymes immobilized with calcium alginate-chitosan beads and then fractionated and purified. The antioxidant and antihypertensive activities of the CP fractions were screened by in vitro and in vivo assays. The in vivo animal studies using spontaneously hypertensive rats (SHRs) confirmed the antihypertensive effects of the CP, and its angiotensin I-converting enzyme (ACE) inhibitory activity was retained after thermal treatment and simulated gastrointestinal digestion. The primary structure of CP-2-1 was identified by RP-HPLC-MS/MS and the amino acid sequence was determined as M-I/L-P-P with the molecular weight of 452.3 Da. CP-2-1 showed effective antioxidant and ACE inhibitory activities (IC50 values of 220 μg mL −1 and 70.32 μg mL −1, respectively) and it might be a potential candidate for antioxidant functional food or pharmaceuticals for hypertension.